2014
DOI: 10.1542/peds.2013-4115
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment Among Area Youth After the Boston Marathon Bombing and Subsequent Manhunt

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Research in the aftermath of large-scale terrorist attacks shows that exposed children experience numerous negative psychological sequelae, including increased emotional difficulties, posttraumatic stress, and significant attack-related life disruptions. WHAT THIS STUDY ADDS:Most research on terrorism-exposed youth examines large-scale terrorism. Limited work examines reactions to terrorism of the scope of the marathon attack, and the extraordinary manhunt and shelter-in-place war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 19 publications
7
51
1
Order By: Relevance
“…As reported elsewhere (Comer et al, in press), childrenā€™s clinical scores, on average, fell within normative ranges, although parents of Marathon-attending children reported greater posttraumatic stress, conduct problems, peer problems, and total difficulties, and the proportion of youth with likely PTSD was roughly 6 times higher among Marathon-attending, than non-attending, youth.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…As reported elsewhere (Comer et al, in press), childrenā€™s clinical scores, on average, fell within normative ranges, although parents of Marathon-attending children reported greater posttraumatic stress, conduct problems, peer problems, and total difficulties, and the proportion of youth with likely PTSD was roughly 6 times higher among Marathon-attending, than non-attending, youth.…”
Section: Resultssupporting
confidence: 78%
“…Indeed, the present study found caregiver distress significantly predicted greater child posttraumatic stress, overall difficulties, emotional problems, hyperactivity/inattention, peer problems, and lower prosocial behavior even after accounting for the extent to which children and caregivers were exposed to similar potentially traumatic events. These findings also help clarify evidence that childrenā€™s responses to disasters are heterogeneous (e.g., Comer et al, in press; Furr et al, 2010; Hoven et al, 2005; La Greca et al, 2013; Shahar, Cohen, Grogan, Barile, & Henrich, 2009). Family factors, such as caregiver distress, appear to explain some of the heterogeneity observed across childrenā€™s responses.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Communities should also host "town meetings" in which community members can ask questions to health experts who can respond with suggestions, which can be an effective strategy for dissemination of information (14). Special consideration should be taken when addressing concerns or problems experienced by young children, whose exposure to the incident through the media and constant retelling of events should be limited (15). An important aspect of successful recovery from traumatic events is resuming normal life as soon as possible and using social support to discuss reactions (14).…”
mentioning
confidence: 99%